Masseteric nerve for gracilis muscle re-innervation in unilateral facial palsy: Impact on quality of life. Issue 7 (July 2017) - Bianchi, B.; Ferri, A.; Poddi, V.; Bergonzani, M.; Pedrazzi, G.; Ferrari, S.; Sesenna, E.
Abstract: Background: Unilateral established or congenital facial palsies are usually treated with neuromuscular transplantation to reanimate the impaired side of the face. One of the most debated points is the motor nerve to choose for the reinnervation of the transplant. Contra-lateral healthy facial nerve is usually preferred, but in selected cases motor nerve to masseter is considered a valuable option. However only a few clinical studies focused on quality of life in this subset of patients are available in literature. Methods: Twenty patients treated for established or congenital unilateral facial palsy reanimated with gracilis muscle transplant reinnervated with masseteric nerve were retrospectively analyzed. The FDI questionnaire on quality of life was administered before and after surgery and statistical analysis of results was conducted to score changes. Results: Overall results of the questionnaire resulted in a statistically significant improvement after surgery, with a p value of 0.05. Conclusion: Facial animation with gracilis muscle transplant re-innervated with masseteric nerve is a safe and reliable procedure in selected unilateral facial palsy patients. Results reported here confirm that surgery mainly improves the functional aspects of a patient's daily life quality, while the impact on social interactions and self-perception is less significant. The comparison of these results with those obtained in patients treated with gracilis muscle transplant re-innervated via contralateral facial nerve suggests that spontaneity is probably highly relevant to improve social aspects of QOL in this subset of patients.